Investigation of the Polyphenol Recovery of Overripe Banana Peel Extract Utilizing Cloud Point Extraction - Vassilis Athanasiadis; Theodoros Chatzimitakos; Martha Mantiniotou; Dimitrios Kalompatsios; Eleni Bozinou; Stavros I. Lalas (Eng, 2023)
Consuming fruits and vegetables necessitates discarding the inedible parts, which raises issues such as waste management and contamination of the environment. Numerous studies have been conducted in recent years in an effort to identify alternatives that reduce the negative effects of food and agricultural waste. This study aims to investigate the polyphenol recovery and the antioxidant capacity of overripe banana peel through cloud point extraction (CPE), which is a green method. The optimal conditions of the CPE were three steps of CPE with 10% w/v lecithin, which was used as surfactant, pH 7, and a salt concentration of 15% at 45 °C for 20 min. The total polyphenol content (TPC) was determined to be 541.25 mg GAE/L, the total flavonoid content (TFC) was determined to be 226.38 mg RtE/L, and FRAP and DPPH assays were found to be 2.52 and 2.91 mmol AAE/L, respectively. According to the results, the antioxidant compounds from banana peels can effectively be extracted with the proposed CPE procedure. The as-prepared extracts can potentially be used as food additives to improve human well-being and even as feed additives for a similar purpose.